SORPTION OF PHOSPHOROUS DERIVATIVES OF CYANINE DYES ONTO FILMS BASED ON SILICA AND CATION-EXCHANGE POLYELECTROLYTES: UDC: 543.4:543.544 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
It was demonstrated the possibility of modification of the composite films based on silica and cation-exchange polyelectrolytes with dioxyazaphosphocane derivatives of cyanine dyes. Optimal conditions of the dyes immobilization were found. The modified films were shown to be perspective for sorption-luminescent determination of alkaline-earth metal ions i.e. Calcium.
Keywords: -